Sternectomy for Treating Advanced Non-Melanoma Skin Cancer - Victor Emmanuel Gadelha Pinheiro; Bianca Rohsner Bezerra; Luís Arthur Brasil Gadelha Farias; Irapuan Teles de Araujo Filho; Marcio Ribeiro Studart da Fonseca (Journal of Skin Cancer)
Introduction. Skin cancer is a rare indication of sternectomy. Our goal is to report the clinical course of seven patients who underwent sternectomy for skin cancer. Methods. The survey data were collected from medical records of patients treated between 2008 and 2018 at Ceará Cancer Institute. Results. All patients had prolonged sunlight exposure and average disease time of two years and age of 60 years. Most patients recovered favorably after treatment with prolonged survival. Conclusion. Sternectomy remains an option with curative purposes for locally advanced skin cancer.